ANÁLISE DA VIABILIDADE DO USO DE GARRAFA PET TRITURADA COMO SUBSTITUIÇÃO AO AGREGADO NATURAL EM ARGAMASSAS - Franz, Lucas; Stolz, Carina (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The main objective of this research is to evaluate the influence and viability of natural aggregates partial substitution by polyethylene terephthalate (PET) residues in mortars. Specifically, it was evaluated the properties of mortars in fresh and hardened state, with different PET waste granulometric composition. In order to achieve the work objectives, the aggregates were characterized and then an experimental matrix were developed. Mortars with 1:3 (cement: aggregate) mix proportion were produced. First of all, a reference mortar, only with natural aggregate, and then four mortars with different PET waste granulometry, called Flake, Powder, Fine and Mix. The results indicated that, in relation to mortar's workability, there was an influence of PET waste addition, probably related to the shape of the grains and a number of fines particles. It was observed a decrease in the flexural and compressive strength. Also, the mortar's density decreased as the granulometry with the higher number of fines was incorporated. Thus, among all the granulometry from PET waste incorporated in the mortars, the Flake appears to be one of the best alternatives for a more noble destination of the material, adding value and reducing environmental impacts.